Empowering Women under Social Constraints: Evidence from a Field Intervention in Rural Egypt - Ahmed Elsayed; Rania Roushdy (Institute of Labor Economics (IZA), 2017)
Women in the MENA region are economically and socially disempowered. High youth unemployment rates together with discriminatory social norms drive them to limit their investment in human capital. We evaluate a large-scale intervention attempting to relax human capital constraints for women by offering vocational, business and life skills training in 30 villages in rural Egypt. Relative to women in the control villages, the intervention increased the likelihood of treated women engaging in income-generating activities, driven by an increase in self-employment. Treated women also became more likely to have future business aspirations. However, their intra-household decision-making and gender equality attitudes were not affected by the intervention. We show that these results mask heterogeneous effects in terms of background characteristics and initial levels of social empowerment. We find no evidence of positive spillover effects for the program within treated villages and, more importantly, no evidence of different pre-trends in employment between the treated and control groups prior to the intervention.
Keywords: I25; J24; O12; 330; empowerment of women; field intervention; Egypt